Mental ill-health among health and social care professionals: an analysis using administrative data - Curran, Emma; Rosato, Michael; Ferry, Finola; Leavey, Gerard (International Journal of Population Data Science, 2021)
Objective Health and Social Care (HSC) workers are at high risk of job-related stress, burnout and mental ill-health. This study examines differences in self-reported mental health and psychotropic medication uptake across HSC occupational groups. Method Northern Ireland (NI) data linkage study of people working in the Health and Care sector, aged between twenty and sixty-four years, enumerated at the 2011 Northern Ireland Census and living in private households, and their uptake of prescribed psychotropic medications during 2011-2012 (using data derived from routine electronically captured information on prescriptions issued within the NHS and linked at an individual level using a NI-specific Health and Care key identifier). Comparing HSC workers with all those professionals not involved in HSC occupations, we used multinomial logistic regression to examine (a) self-reported chronic mental illness and (b) uptake of psychotropic medication by occupational groups adjusting for age, sex and socio-demographic circumstance. Results When compared against other professionals highest risks for mental health problems (associated with psychotropic prescription uptake) were associated with nursing/midwifery (OR = 1.25: 95{%}CI = 1.17-1.33; OR = 1.84: 1.58-2.15 for females and males respectively), welfare (OR = 1.34: 1.21-1.48; OR = 1.71: 1.44-2.03) and formal caregiving roles (OR = 1.42: 1.31-1.53; OR = 1.70: 1.50-1.91), again for females/males respectively). These higher risk professions record notable increases in psychotropic medication use. Conclusion Working in the Health and Social Care sector, irrespective of gender, may be more stressful than other jobs. Additionally, self-reported mental ill-health and psychotropic medication treatment both appear to be associated with social class inequity.